Creation of a database for the compilation of digital land Cadastral maps. - Khakimova Kamola Rakhimjonovna; G‘ofurov Xalimjon Voxidjon o‘g‘li (Zien Journals, 2023)
This article provides information on the creation of a database for the creation of digital land cadastral maps, a group of errors that occur when creating a database
Keywords: digital; cadastre; map; GAT